Allosteric coupling between PIP 2 and Ca 2+ binding sites gates TMEM16A channels - Jie Xu; Ana Santa-Cruz; Aishwarya Chandrashekar; Takeharu Kawano; R. Charles Kissell; Mehreen Zaka; Zhe Zhang; Meng Cui; Diomedes E. Logothetis; Leigh D. Plant (Proceedings of the National Academy of Sciences, 2026)
TMEM16A channels conduct Ca 2+ -activated Cl − currents that underlie essential physiological processes including epithelial secretion, smooth muscle contraction, and sensory transduction. Channel activation requires both intracellular Ca 2+ and the signaling phospholipid phosphatidylinositol 4,5-bisphosphate (PIP 2 ), yet the molecular basis of this dual regulation has remained unclear. Using gating molecular-dynamics simulations and structure-guided electrophysiology, we show that PIP 2 and Ca 2+ cooperatively gate TMEM16A through an allosterically coupled electrostatic network centered on the α4 helix. Specific PIP 2 headgroup phosphate interactions are essential for coupling Ca 2+ binding to channel opening, while the PIP 2 acyl chains engage hydrophobic surfaces of the helix to stabilize the open conformation. Disrupting either component of this lipid–protein interface reduces apparent PIP 2 affinity and impairs activation, whereas long-chain PIP 2 fully restores wild-type activity. These interactions act in concert with Ca 2+ -dependent structural rearrangements that widen the conduction pathway and enable Cl − permeation. Our findings establish that both the headgroup phosphates and acyl chains of PIP 2 play indispensable and complementary roles in TMEM16A gating. This mechanism defines a cooperative lipid–ion activation process that provides a general framework for understanding phosphoinositide regulation of ion channels and offers opportunities for structure-based design of TMEM16A modulators.